ANALISIS AMENITAS DAN DAYA DUKUNG WISATA PANTAI PASIR TIKU DI KECAMATAN TANJUNG MUTIARA KABUPATEN AGAM PROVINSI SUMATERA BARAT - Mutia Ayulanda; Sri Mariya (DEPARTEMEN GEOGRAFI FIS UNP, 2021)
The purpose this research are: 1). Analyzing the tourist amenities of Pasir Tiku Beach 2). Analyzing the physical carrying capacity of the Pasir Tiku Beach tourism. This type of research is classified as a qualitative descriptive study. The informants of this research are the head of the development of tourism destinations and tourist attractions in the Agam Regency youth and sports tourism office, the manager of the Pasir Tiku Beach tourism object, 90 visitors and eight traders of the Pasir Tiku Beach tourist attraction. Data collection techniques by interview and documentation. Data analysis techniques by reducing, displaying data and verifying data. The data validity technique used credibility, increased persistence, and triangulation. The results showed that 1). The amenities of Pasir Tiku Beach are fairly complete, of the eleven indicators of supporting facilities, only three facilities are missing, namely electricity, a parking lot and a souvenir shop. 2). Analysis of the carrying capacity of the Pasir Tiku Beach tourist attraction is included in the excess number of visitors based on capacity. This is based on the average number of visitors who traveled to Tiku sand beach attractions in the past five years, namely 163 people per day, so this number exceeds the capacity that should be at the Tiku Sand Beach tourist attraction. The capacity should be 105 people per day per 2.7 hours. With a number that exceeds its capacity, what the manager needs to do is to limit the number of visitors who come to Tiku sand beach attractions.